Interaction of Pulses of Different Duration with Chemically Prepared Silver Nanoparticles: Analysis of Optical Nonlinearities - Ke Zhang (Journal of Nanomaterials, 2019)
The nonlinear optical properties of the aqueous solutions of silver nanoparticles (Ag NPs) prepared by chemical reduction method are analyzed using femtosecond and picosecond pulses at different wavelengths. In the case of 800 and 400 nm, the growths of nonlinear absorption and nonlinear refraction with the increase of Ag NP concentration, as well as a change at the signs of nonlinear optical processes, are determined. The nonlinear absorption coefficient and nonlinear refractive index of Ag NP solutions measured using picosecond pulses were a few orders of magnitude larger than those in the case of femtosecond probe pulses. We also demonstrate the optical limiting properties of Ag NPs using 800 nm, 60 fs pulses.